2020
DOI: 10.1016/j.jgo.2019.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Cost differential associated with hospice use among older patients with multiple myeloma

Abstract: Background: Hospice is an effective end-of-life care approach for patients with incurable illnesses such as multiple myeloma; however, it has been historically underutilized. In addition to improving quality of life, hospice enrollment reduces healthcare spending in many incurable illnesses but this has been unstudied in the myeloma population to date. Material and Methods: Retrospective analysis of myeloma cases diagnosed from 2007 to 2013 in the Surveillance, Epidemiology, and End Results (SEER)-Medicare lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our study found that, compared with LSTs, ICHC had signi cantly fewer MADDCs and MTDCs incurred in the last 2 days (P < 0.01), with the decrease rate of about 30%, suggesting that ICHC can reduce medical care, resource utilization rates, and cost. This is consistent with other reports on HC/PC which also greatly reduced medical expenses [38][39][40] . Other studies mainly focused on the treatment impact on overall medical insurance costs, but not on ADDCs.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that, compared with LSTs, ICHC had signi cantly fewer MADDCs and MTDCs incurred in the last 2 days (P < 0.01), with the decrease rate of about 30%, suggesting that ICHC can reduce medical care, resource utilization rates, and cost. This is consistent with other reports on HC/PC which also greatly reduced medical expenses [38][39][40] . Other studies mainly focused on the treatment impact on overall medical insurance costs, but not on ADDCs.…”
Section: Discussionsupporting
confidence: 93%
“…Fifteen US studies and six non-US studies reported on age and disparities in access to treatment (Supplementary Table 3 ), with the majority showing that increasing age reduced access to treatment, including stem cell transplantation. Twelve US studies (Supplementary Table 4 ) and one study each in Europe and Canada reported on sex and access to treatment, most identifying better access to treatment in favor of men [ 31 , 39 , 40 , 42 , 43 , 47 , 54 , 65 , 80 ]. Access to stem cell transplantation was also reported to be worse in females [ 31 , 40 ], except for one US study which reported that more Black women than Black men underwent autologous stem cell transplantation [ 26 ] and one Canadian study reporting no significant effect of sex on access to autologous stem cell transplantation [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve US studies and seven non-US studies reported on socioeconomic status and access to treatment (Supplementary Table 6 ), with mixed results. Lower socioeconomic status, whether defined by general socioeconomic status, household income, education level, or insurance status, was generally associated with worse access to treatment, including stem cell transplantation[ 27 , 36 , 37 , 39 , 40 , 43 , 50 , 54 , 58 , 72 , 80 , 88 , 93 , 97 ], although this was not a universal finding [ 36 , 42 , 43 , 47 , 50 , 54 , 58 , 60 , 66 , 96 ]. The effects of geography on access to treatment were reported in five US studies (Supplementary Table 7 ) and one study each in Canada and France [ 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the costs of end-of-life care were based on prior work. 35 All costs were converted to 2020 USD using the personal consumption expenditurehealth index. 36…”
Section: Costsmentioning
confidence: 99%